Е-бизнис системи за процесна организациска трансформација и конкурентност на претпријатијата - Мијоска, Марина (Економски факултет, УКИМ, Скопје, 2015)
We are living in exponential times, when everything is changing rapidly. This continuously changing environment creates pressure for businesses and their managers. In order to survive they need to change as well. Companies are pressured to become more flexible, agile, fast responding and customer oriented. One strategy for achieving these objectives is process orientation. Business process orientation (BPO) and process thinking help management to leverage the potential of the information and communication technologies and the Internet, and hence to implement e-business with a greater success. Extensive literature on business process management suggests that organizations could enhance their overall performance by adopting a process view of business. But, being aware of its business processes is not enough. Managing mature business processes is the new challenge for contemporary management. In this sense, maturity models have been proposed to gradually assess and improve business processes in organizations. Hence, business process management maturity models are becoming the new promising tool for managing successful companies in e-business environment. They become practical tools that assist organizations in achieving business (process) excellence. As the topic became very popular, a proliferation of business process maturity models can be witnessed. Having in mind the importance of transformation towards process oriented organization in e-business environment and of managing mature business processes that lead to improved organizational performance, the main goal of this dissertation is to provide literature review and to test the model that measures the impact of business process orientation on improving organizational performance. For this purpose, data from empirical survey conducted in Macedonian companies is used/collected. Empirical testing is done by structural equation modeling.
E-business systems for process centric organisational transformation and competitiveness of enterprises
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Сашо Јосимовски.
Keywords: e-business, business process orientation, business process management, business process maturity models, organizational performance, structural equation modeling